Layered Potassium Vanadate K0.5V2O5 as a Cathode Material for Nonaqueous Potassium Ion Batteries. (25th May 2018) - Deng, Leqing; Niu, Xiaogang; Ma, Guanshui; Yang, Zhao; Zeng, Liang; Zhu, Yujie; Guo, Lin
Abstract: Nonaqueous potassium ion batteries (KIBs) are one of the emerging electrochemical energy storage technologies due to the abundance of potassium resources, but the difficulties of intercalation of large size K‐ions into electrode materials hinder the development of KIBs. Here, a layered potassium vanadate K0.5 V2 O5 is proposed as a potential cathode material for KIBs. Despite the large size of K‐ions, the as‐fabricated material is capable of delivering a reversible capacity around 90 mAh g −1 at 10 mA g −1 in the voltage range of 1.5–3.8 V (vs K + /K), and also exhibits a fast rate capability with a capacity of 60 mAh g −1 at 200 mA g −1 and good cycling stability with 81% capacity retention after 250 cycles at 100 mA g −1 . Ex situ X‐ray diffraction and X‐ray photoelectron spectroscopy reveal that the layered potassium vanadate exhibits a highly stable and reversible structure change with a transition between V 4+ and V 5+ upon potassiation/depotassiation. Additionally, galvanostatic intermittent titration technique results show that the kinetics of potassiation/depotassiation is mainly determined by K‐ion diffusion in the active material. The present study may open up further exploration of potassium vanadates and other layered transition metal oxides in the field of KIBs. Abstract : A layered potassium vanadate K0.5 V2 O5 is reported as a cathode material for non‐aqueous potassium ion batteries. This material demonstrates good cycling stability and a transition between V 4+ and V 5+ takes place upon potassiation/depotassiation. This study may stimulate further exploration of potassium vanadates and other layered transition metal oxides in the field of potassium ion batteries.